Answer:
The fractional change is [tex]\frac{1}{3}[/tex] % .
Step-by-step explanation:
Given as :
The original fraction = [tex]\dfrac{x}{y}[/tex]
Where numerator = x
Denominator = y
According to question
The numerator decreased by 50%
Let The new numerator = x' = x - 50% of x
I,e x' = x ( 1 - [tex]\frac{50}{100}[/tex])
Or, x' = x ([tex]\frac{100-50}{100}[/tex])
Or, x' = [tex]\frac{50}{100}[/tex] x
or, x' = [tex]\dfrac{x}{2}[/tex] .........A
Again
The new denominator = y' = y - 25% of y
i.e y' = y (1 - [tex]\frac{25}{100}[/tex])
Or, y' = y ([tex]\frac{100-25}{100}[/tex])
Or, y' = y ([tex]\frac{75}{100}[/tex])
Or, y' = [tex]\frac{3 y}{4}[/tex] ............B
So, The new fraction = [tex]\frac{x'}{y'}[/tex] = [tex]\frac{\frac{x}{2}}{\frac{3 y}{4}}[/tex]
Or, [tex]\frac{x'}{y'}[/tex] = [tex]\frac{2 x}{3 y}[/tex]
So, The fractional change = [tex]\frac{1-\frac{2}{3} }{1}[/tex] × 100
Or, The fractional change = [tex]\frac{1}{3}[/tex]× 100
Hence, The fractional change is [tex]\frac{1}{3}[/tex] % . Answer